Improved decision-making and psychophysiological responses in mesial temporal lobe epilepsy after anterior temporal lobectomy - Yağcı, Selin; Korkmaz, Bektaş; ŞANDOR, SERRA (My University, 2018)
The somatic marker hypothesis is an influential model of human decision-making postulating that somatic feedback to the brain enhances decision-making in ambiguous circumstances, i.e. when the probabilities of various outcomes are unknown. The somatic feedback can be measured as autonomic responses, which are regulated by the amygdala. The failure to evoke this somatic feedback, which occurs in patients with amygdala lesions, impairs decision-making. The purpose of this study was to investigate the decision-making behaviour of mesial temporal lobe epilepsy patients with pre- and post-epilepsy surgery to ascertain whether the decision-making abilities of groups can be explained by means of the generation of somatic feedback responses.
Keywords: temporal lobe epilepsy; decision-making; epilepsy surgery; somatic-marker hypothesis; psychophysiology